Structural measurments of degraded trees in the mangrove forest of Bonaire, Dutch Caribbean - Florian Senger; Lucy Gwen Gillis; Sabine Engel (PANGAEA, 2020)
In Lac Bay a 10 m by 10 m plot was established and within each plot tree characteristics were identified and measured. The perimeter at breast height (or 1.3 m) of each tree inside the plot was noted, except for the perimeter of R. mangle species, where measurements were taken at the height of the highest prop root. From the perimeter the diameter at breast height (DBH) was calculated.
In: Senger, F et al. (2020): Impacts of wetland dieback on carbon dynamics: A comparison between intact and degraded mangroves [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.910433